On dynamic packet fragmentation for traffic integration over bandwidth-limited links. (6th January 2009) - Guo, Liang; Lee, Whay Chiou; Lin, Ying-ieh
We consider a home networking system for integrating packetised isochronous and best-effort traffic over a shared link with limited bandwidth, wherein the isochronous traffic comprises multiple isochronous flows, each associated with a periodic packet arrival process having a constant isochronous packet transmission period. In such a system, best-effort packets of variable size can render it impossible to guarantee QoS of the isochronous traffic. We propose a dynamic packet fragmentation method to integrate isochronous and best-effort traffic. In particular, the method supports packet fragmentation with fixed size or variable size packets. We show that the method effectively increases link utilisation and best-effort traffic throughput, without violating the delay and jitter requirements for isochronous traffic.